2023
DOI: 10.1021/acsnano.3c03458
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Sulfur Nanosheets for Dual-Selective Inhibition of Gram-Positive Bacteria

Abstract: Elemental sulfur is the oldest known antimicrobial agent. However, conventional sulfur in the clinic suffers from poor aqueous solubility and limited antibacterial activity, greatly hindering its practical use. Herein, we report a reform strategy coupling dimension engineering with chirality transfer to convert conventional 3D sulfur particles into chiral 2D sulfur nanosheets (S-NSs), which exhibit 50-fold improvement of antibacterial capability and dualselective inhibition against Gram-positive bacteria. Bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Since there are very few reports on the antibacterial properties of sulfur nanosheets, we were eager to investigate the antibacterial effectiveness of BA-exfoliated nanosheets. 58 During the assessment of the exfoliation process, we observed that a longer exfoliation time was required with BA to transform the bulk sulfur. It took 150 min to be exfoliated into nanosheets, and after 180 min, nanodots started to form (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are very few reports on the antibacterial properties of sulfur nanosheets, we were eager to investigate the antibacterial effectiveness of BA-exfoliated nanosheets. 58 During the assessment of the exfoliation process, we observed that a longer exfoliation time was required with BA to transform the bulk sulfur. It took 150 min to be exfoliated into nanosheets, and after 180 min, nanodots started to form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This MIC value is noteworthy and compares favorably with previously reported data on sulfur nanosheets (100 μg mL −1 ). 58 Furthermore, we quantified the ability of these nanosheets to kill bacteria by streaking the treated solution onto agar plates. The concentration at which no bacterial colonies formed on the agar plate indicated the minimum bactericidal concentration (MBC), which was determined to be 31.3 μg mL −1 for the BASNs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3B), in which the peaks at 161.5 eV and 162.6 eV were attributed to zero-valent sulfur and the peaks at 167.5 eV and 168.5 eV can be assigned to the oxidation state of sulfur such as SO 2 À (2p 2/3 ), SO 2 À (2p 1/2 ), or SO 3 2À (2p 2/3 ). 3,14,45 The oxidation state of sulfur arises from the presence of the atmospheric oxygen. Fig.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
“…However, the fabrication of inherently chiral materials remains challenging. Of late, chirality transfer to the conventional sulfur particles (3D structure) into chiral sulfur nanosheets (2D structure) has improved their dispersibility in aqueous medium and antibacterial properties by 50-fold . Notably, the earth-abundant element bulk sulfur has been widely employed in various synthesis techniques as a primary precursor of Sdots and still suffers from a few shortcomings such as complex synthesis procedures.…”
Section: Introductionmentioning
confidence: 99%